Umma : a Korean mom's kitchen wisdom & 100 family recipes - Ahn, Sarah; Ahn, Nam Soon (America's Test Kitchen, 2025)
"Sarah Ahn's viral food videos of her and her mom have captivated millions of viewers with their behind-the-scenes look at Korean cooking and multigenerational home life. This collaboration is now a must-have cookbook blending the emotional intimacy of Crying in H Mart with practical culinary advice from Nam Soon's lifetime of kitchen experience. The recipes are framed by mother-daughter conversations that are funny, profound, and universally relatable-plus all the food is backed by the recipe-testing power of America's Test Kitchen"--